Effects of 12 Weeks of Interval Block Resistance Training Versus Circuit Resistance Training on Body Composition, Performance, and Autonomic Recovery in Adults: Randomized Controlled Trial - Héctor Fuentes-Barría; Raúl Aguilera-Eguía; Juan Maureira-Sánchez; Miguel Alarcón-Rivera; Victor Garrido-Osorio; Olga Patrica López-Soto; Juan Alberto Aristizábal-Hoyos; Lissé Angarita-Davila; Diana Rojas-Gómez; Valmore Bermudez; Cherie Flores-Fernández; Ángel Roco-Videla; et al. (Journal of Functional Morphology and Kinesiology, 2025)
Objectives: Interval block resistance training (IBRT) and circuit resistance training (CRT) are periodization models aimed at enhancing neuromuscular and metabolic adaptations. This study aims to evaluate the effects of a 12-week IBRT program compared to CRT on body composition, muscle strength, speed, functional capacity, and autonomic recovery in young Chilean adults. Methods: A randomized, parallel, double-blind study was conducted with 30 participants assigned to IBRT (n = 15) or CRT (n = 15). Assessments included body mass index (BMI), waist circumference, right-hand grip strength, the running anaerobic sprint test (RAST), the 6 min walk test (6 MWT), and heart rate variability (HRV) indices: low-frequency to high-frequency ratio (LF/HF) and root mean square of successive differences (RMSSD, a time-domain HRV metric reflecting parasympathetic activity). Statistical analyses included t-tests and ANCOVA. Results: Groups were similar in age (IBRT: 25.2 ± 3.19; CRT: 23.27 ± 3.69, p = 0.14) and BMI (IBRT: 21.56 ± 2.22; CRT: 22.36 ± 1.70 kg/m2, p = 0.40). Both groups improved significantly in waist circumference (IBRT: −1.85%; CRT: −2.37%), grip strength (IBRT: +5.47%; CRT: +4.02%), RAST (IBRT: −2.67%; CRT: −1.04%), 6 MWT (IBRT: +4.53%; CRT: +2.17%), LF/HF (IBRT: −11.43%; CRT: −5.11%), and RMSSD (IBRT: +5.36%; CRT: +3.81%) (all p ≤ 0.01). IBRT produced significantly greater gains in 6 MWT (B = 19.51, 95% CI: 0.79 to 38.23, p = 0.04). Conclusions: Both IBRT and CRT effectively improved body composition, muscle strength, speed, functional capacity, and autonomic recovery. However, IBRT demonstrated a superior effect on aerobic capacity.